The Stress on the Medical Practitioners Through the Covid-19 Pandemic in the City of Madina - Aloufi, Mona Ateg Salamah; Kurdi, Sandi Farooq (Journal of Educational and Psychological Sciences, 2022)
This study aimed to identify the psychological stress level among health practitioners (Doctors/Nurses) during the Coronavirus pandemic in Al-Madinah, and to identify the statistically significant differences according to the demographic variables (gender, experience, occupation, age). The researcher used the descriptive method, and a questionnaire was used of the psychological stress which is a component of four dimensions (psychological, physical, occupational, family). This study was applied on a random sample of (305) male and female of doctors and nurses. The study results showed the occupational dimension had the highest ratio in terms of psychological stress. Additionally, there are statistically significant differences in the psychological stress level among health practitioners due to the sex variable in favor of females, due to the occupational variable in favor of nursing, and due to the age variable in favor of younger. However, there are no statistically significant differences due to the variable of experience. The researcher recommends the importance of establishing educational awareness programs for health practitioners to relieve work pressure, creating appropriate working conditions, and allocating specialized counselors by the Ministry of Health in hospitals and health centers to support health practitioners psychologically during the pandemic period.
Keywords: Stresses; Health Practitioners; Coronavirus pandemic